2006
DOI: 10.1007/s00774-006-0690-3
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal expression of Col X, PTHrP, TGF-β, bFGF, and VEGF in cartilage with Kashin–Beck disease

Abstract: The purpose of the current study was to investigate the abnormal expression of Col X, PTHrP, TGF-beta, bFGF, and VEGF in cartilage from patients with Kashin-Beck disease (KBD) to understand the pathogenesis of chondronecrosis in KBD. Articular cartilage and growth plate cartilage collected were divided into four groups: control children (8 samples, 5 cases), KBD children (19 samples, 9 cases), control adults (8 samples, 6 cases), and KBD adults (16 samples, 15 cases). The presence of PTHrP, TGF-beta1, bFGF, VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 40 publications
5
45
0
Order By: Relevance
“…Therefore, the damage of epiphyseal plate cartilage is the most important characteristic in the diagnosis of KBD [25]. Besides, chondrocyte dedifferentiation, deep zone chondronecrotic changes and abnormal type-X collagen, TGF-b, PTHrP, bFGF and VEGF staining patterns have been noticed in KBD cartilage [26].…”
Section: Cartilage Damagementioning
confidence: 99%
“…Therefore, the damage of epiphyseal plate cartilage is the most important characteristic in the diagnosis of KBD [25]. Besides, chondrocyte dedifferentiation, deep zone chondronecrotic changes and abnormal type-X collagen, TGF-b, PTHrP, bFGF and VEGF staining patterns have been noticed in KBD cartilage [26].…”
Section: Cartilage Damagementioning
confidence: 99%
“…Additionally, FGF receptors are important in regulating factors in cartilage growth. A recent study found that dysfunction of FGF receptor 3 resulted in abnormal chondrogenic differentiation and matrix synthesis (Qi et al 2014), which was also observed in KBD cartilage (Guo et al 2006;Wang et al 2008). Biological function studies of FGF12 were limited.…”
Section: Discussionmentioning
confidence: 93%
“…The histological study of KBD showed that type X collagen expression was reduced in areas of chondrocyte necrosis in the deep zone of KBD articular cartilage, indicating changes in terminal chondrocyte differentiation. 25 Although the pathology of KBD may be explained by the effect of mycotoxins, and different species of fungi produce a wide range of mycotoxins, a low nutrition diet may be involved in the etiology of KBD. 16,21,26 In the normal diet, some antioxidant materials, including vitamin C, vitamin E, and selenium can inhibit or relieve cytotoxicity of T-2 toxin.…”
Section: Discussionmentioning
confidence: 99%